Cyclopropanations via Heme Carbenes: Basic Mechanism and Effects of Carbene Substituent, Protein Axial Ligand, and Porphyrin Substitution - Wei, Yang (J Am Chem Soc, 2017)
[Image: see text] Catalytic carbene transfer to olefins is a useful approach to synthesize cyclopropanes, which are key structural motifs in many drugs and biologically active natural products. While catalytic methods for olefin cyclopropanation have largely relied on rare transition-metal-based catalysts, recent studies have demonstrated the promise and synthetic value of iron-based heme-containing proteins for promoting these reactions with excellent catalytic activity and selectivity. Despite this progress, the mechanism of iron-porphyrin and hemoprotein-catalyzed olefin cyclopropanation has remained largely unknown. Using a combination of quantum chemical calculations and experimental mechanistic analyses, the present study shows for the first time that the increasingly useful C=C functionalizations mediated by heme carbenes feature an Fe(II)-based, nonradical, concerted nonsynchronous mechanism, with early transition state character. This mechanism differs from the Fe(IV)-based, radical, stepwise mechanism of heme-dependent monooxygenases. Furthermore, the effects of the carbene substituent, metal coordinating axial ligand, and porphyrin substituent on the reactivity of the heme carbenes was systematically investigated, providing a basis for explaining experimental reactivity results and defining strategies for future catalyst development. Our results especially suggest the potential value of electron-deficient porphyrin ligands for increasing the electrophilicity and thus the reactivity of the heme carbene. Metal-free reactions were also studied to reveal temperature and carbene substituent effects on catalytic vs noncatalytic reactions. This study sheds new light into the mechanism of iron-porphyrin and hemoprotein-catalyzed cyclopropanation reactions and it is expected to facilitate future efforts toward sustainable carbene transfer catalysis using these systems.